Accuracy and precision of apparent diffusion coefficient measurements on a 1.5 T MR-Linac in central nervous system tumour patients. (November 2021) - Lawrence, Liam S.P.; Chan, Rachel W.; Chen, Hanbo; Keller, Brian; Stewart, James; Ruschin, Mark; Chugh, Brige; Campbell, Mikki; Theriault, Aimee; Stanisz, Greg J.; MacKenzie, Scott; Myrehaug, Sten; et al.
Highlights: Apparent diffusion coefficient (ADC) from MR-Linac in brain was validated. ADC from MR-Linac and diagnostic scanner similar in tumours, white/grey matter. Repeatability of MR-Linac ADC is similar to that of diagnostic scanners. Daily ADC changes in high-grade gliomas are detectable with MR-Linac. Abstract: Background and purpose: MRI linear accelerators (MR-Linacs) may allow treatment adaptation to be guided by quantitative MRI including diffusion-weighted imaging (DWI). The aim of this study was to evaluate the accuracy and precision of apparent diffusion coefficient (ADC) measurements from DWI on a 1.5 T MR-Linac in patients with central nervous system (CNS) tumours through comparison with a diagnostic scanner. Materials and methods: CNS patients were treated using a 1.5 T Elekta Unity MR-Linac. DWI was acquired during MR-Linac treatment and on a Philips Ingenia 1.5 T. The agreement between the two scanners on median ADC over the gross tumour/clinical target volumes (GTV/CTV) and in brain regions (white/grey matter, cerebrospinal fluid (CSF)) was computed. Repeated scans were used to estimate ADC repeatability. Daily changes in ADC over the GTV of high-grade gliomas were characterized from MR-Linac scans. Results: DWI from 59 patients was analyzed. MR-Linac ADC measurements showed a small bias relative to Ingenia measurements in white matter, grey matter, GTV, and CTV (bias: –0.05 ± 0.03, –0.08 ± 0.05, –0.1 ± 0.1, –0.08 ± 0.07 μm 2 /ms). ADC differed substantially in CSF (bias: –0.5 ± 0.3 μm 2 /ms). The repeatability of MR-Linac ADC over white/grey matter was similar to previous reports (coefficients of variation for median ADC: 1.4%/1.8%). MR-Linac ADC changes in the GTV were detectable. Conclusions: It is possible to obtain ADC measurements in the brain on a 1.5 T MR-Linac that are comparable to those of diagnostic-quality scanners. This technical validation study adds to the foundation for future studies that will correlate brain tumour ADC with clinical outcomes.